2013
DOI: 10.1177/1087057112456878
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput FRET Assay Yields Allosteric SERCA Activators

Abstract: Using fluorescence resonance energy transfer (FRET), we performed a high-throughput screen (HTS) in a reconstituted membrane system, seeking compounds that reverse inhibition of sarco-/endoplasmic reticulum Ca-ATPase (SERCA) by its endogenous regulator, phospholamban (PLB). Such compounds have long been sought to correct aberrant Ca2+ regulation in heart failure. Donor-SERCA was reconstituted in phospholipid membranes with or without acceptor-PLB, and FRET was measured in a steady-state fluorescence microplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
97
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 37 publications
5
97
2
Order By: Relevance
“…Here we assessed the metabolic effects of a small molecule SERCA2 activator, CDN1163, that acts directly on SERCA enzyme probably via allosteric mechanism to activate SERCA2's Ca 2ϩ -ATPase activity and improve Ca 2ϩ homeostasis (16). We demonstrate that SERCA2b activation via CDN1163 attenuates ER stress, ameliorates mitochondrial efficiency, and improves glucose and lipid metabolism.…”
mentioning
confidence: 99%
“…Here we assessed the metabolic effects of a small molecule SERCA2 activator, CDN1163, that acts directly on SERCA enzyme probably via allosteric mechanism to activate SERCA2's Ca 2ϩ -ATPase activity and improve Ca 2ϩ homeostasis (16). We demonstrate that SERCA2b activation via CDN1163 attenuates ER stress, ameliorates mitochondrial efficiency, and improves glucose and lipid metabolism.…”
mentioning
confidence: 99%
“…We hypothesize that this TR-FRET approach can be used as a tool to screen for compounds that rescue defects in actomyosin structure and function. Small-molecule modulators of actomyosin structural dynamics represent potential leads for future drug development, and this search is greatly facilitated by recent developments in high-throughput FRET-based screening methods, which measure the effects of compounds on the distance between donor and acceptor probes on interacting proteins (1,(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…45,46 Further, a high-throughput fluorescence resonance energy transfer assay has been used to find allosteric SERCA2a activators capable of decreasing SERCA2a/PLN-derived fluorescence resonance energy transfer. 47 In this study, several compounds previously reported to correct aberrant Ca 2+ regulation in HF were shown to activate SERCA2a activity, thus validating the mechanism of action for these drugs.…”
mentioning
confidence: 75%